NiSn Atomic Pair on an Integrated Electrode for Synergistic Electrocatalytic CO2 Reduction. Issue 13 (8th February 2021) - Xie, Wenfu; Li, Hao; Cui, Guoqing; Li, Jianbo; Song, Yuke; Li, Shijin; Zhang, Xin; Lee, Jin Yong; Shao, Mingfei; Wei, Min
Abstract: The development of efficient electrocatalysts for the CO2 reduction reaction (CO2 RR) remains a challenge. Demonstrated here is a NiSn atomic‐pair electrocatalyst (NiSn‐APC) on a hierarchical integrated electrode, which exhibits a synergistic effect in simultaneously promoting the activity and selectivity of the CO2 RR to formate. The NiSn atomic pair consists of adjacent Ni and Sn, each coordinated with four nitrogen atoms (N4 ‐Ni‐Sn‐N4 ). The as‐prepared NiSn‐APC displays exceptional activity for the CO2 RR to formate with a turnover frequency of 4752 h −1, a formate productivity of 36.7 mol h −1  gSn −1 and an utilization degree of active sites (57.9 %), which are superior to previously reported single‐atomic catalysts. Both experimental data and density‐functional theory calculations verify the electron redistribution of Sn imposed by adjacent Ni, which reduces the energy barrier of the *OCHO intermediate and makes this potential‐determining step thermodynamically spontaneous. This synergistic catalysis provides a successful paradigm for rational design and preparation of atomic‐pair electrocatalysts with enhanced performance. Abstract : A NiSn atomic‐pair electrocatalyst (NiSn‐APC) that consists of adjacent Ni and Sn, each coordinated with four nitrogen atoms (N4 ‐Ni‐Sn‐N4 ), has been synthesized. By virtue of the synergistic effect and the enhanced utilization degree of the active site, NiSn‐APC exhibits outstanding electrocatalytic activity and selectivity for the CO2 reduction reaction (CO2 RR) to formate.